2020
DOI: 10.1109/tbme.2019.2914517
|View full text |Cite
|
Sign up to set email alerts
|

Perceptual Limits of Optical See-Through Visors for Augmented Reality Guidance of Manual Tasks

Abstract: Objective: The focal length of available optical seethrough (OST) head-mounted displays (HMDs) is at least 2 m therefore, during manual tasks, the user eye cannot keep in focus both the virtual and real content at the same time. Another perceptual limitation is related to the vergence-accommodation conflict (VAC), this latter being present in binocular vision only. This paper investigates the effect of incorrect focus cues on the user performance, visual comfort and workload during the execution of augmented r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
110
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 125 publications
(117 citation statements)
references
References 36 publications
7
110
0
Order By: Relevance
“…Our results fall in this range. On the other hand, our results from the FF scenario on the Y -axis (TED values close to the 6 mm range) corroborate with results obtained by Condino et al [8]. These results emphasize the importance for sightline awareness and correction when using the HoloLens glasses at surgery (Fig.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our results fall in this range. On the other hand, our results from the FF scenario on the Y -axis (TED values close to the 6 mm range) corroborate with results obtained by Condino et al [8]. These results emphasize the importance for sightline awareness and correction when using the HoloLens glasses at surgery (Fig.…”
Section: Discussionsupporting
confidence: 92%
“…Overall, the literature presents error ranges from 0 to 10 mm by using diverse navigation and accuracy measurement methods on different surgical specialties with the Microsoft HoloLens [8,28,29,[32][33][34]. This collective experimental heterogeneity makes it cumbersome to pinpoint the crucial elements that create such data variability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The human eye is not able to accommodate to proper focus both the real world and the virtual content, and this focus rivalry is incompatible with its use as aid to manual activities [9].…”
Section: Expert Commentarymentioning
confidence: 99%
“…The availability of powerful and user-friendly AR HMDs leveraged the development of many demonstrators for open surgery but without any actual clinical result. In a recent paper, we showed that general-purpose AR HMDs are not yet ready to be routinely used in surgery [9] and the media raised doubtful questions about the dead end of AR HMDs for surgery.…”
Section: Introductionmentioning
confidence: 99%